2008
DOI: 10.1177/10598405080240010401
|View full text |Cite
|
Sign up to set email alerts
|

Program Strategies for Adolescent Smoking Cessation

Abstract: School nurses who work with adolescents are in an ideal position to promote smoking cessation. This opportunity is important because research suggests teens who smoke are likely to become habitual smokers. This study characterizes adolescents' patterns and levels of smoking, describes adolescents' perceptions toward smoking, and delineates quit strategies that may prove helpful for adolescents who attempt smoking cessation. Results suggest adolescent smokers have highly variable patterns and levels of smoking.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Youth who smoke are more likely to believe it makes them more appealing to others, as demonstrated by the positive association between the behavior and the perception of making one appear more grown up, cool, or attractive (Carpenter et al., ; Chang, ; Fritz, Wider, Hardin, & Horrocks, ; Parkinson et al., ). Data confirm that youth who smoke believe it is helpful in social and stressful situations.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Youth who smoke are more likely to believe it makes them more appealing to others, as demonstrated by the positive association between the behavior and the perception of making one appear more grown up, cool, or attractive (Carpenter et al., ; Chang, ; Fritz, Wider, Hardin, & Horrocks, ; Parkinson et al., ). Data confirm that youth who smoke believe it is helpful in social and stressful situations.…”
Section: Resultsmentioning
confidence: 99%
“…For example, multiple authors found that perceived benefits of smoking include a feeling of belonging or increased popularity (Chang, ; Fritz et al., ; Schleicher, Harris, Catley, Harrar, & Golbeck, ; van Zundert et al., ). Another factor associated with smoking among youth is the perception that it is common and accepted (Fritz et al., ; Parkinson et al., ). Ling et al () found an association between smoking and advertising receptivity among young adults, which could have an attitudinal component.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations